Interactions of State and NKO: Possibility, Mechanisms, Problem and the Method of Their Solution - A. N. Chernyshov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the problems of the interrelations of the organs of state and municipal control with the public noncommercial organizations (NPO) are analyzed. Are represented the theoretical and practical studies, which characterize specific character NPO as the subject of social relations, the nature of control of their functioning and development. Article is aimed at the complex idea of the nature of the cooperation of state and noncommercial public organizations by way the disclosure of potential and models of the partner relations of state and NPO; the development of the existing within the framework given relations of problems in modern Russia and the determination of the methods of their solution.. A study is carried out with the use of methods of lawful, organizationalfunctional and problematic analysis on the basis of complex and systems approaches. Classification NPO is carried out and the need for the calculation of this classification with the selection of the most optimum mechanisms of the collaboration of authority with them is substantiated. Dana is the characteristic of the basic directions of the government control of public noncommercial sector and guarantee of partner relations of authority and NPO. Are represented the basic models of interaction of authority and NPO within the framework of direct government control, also, on the basis of partner relations. Is substantiated the priority of the realization of interaction of authority and NPO at the regional and municipal levels. Special significance for state and society of socially oriented NPO is determined. Are isolated and described the problems of the realization of the potential “third sector” in the interrelations of authority and NPO. Are designated for solving the data of problems the measures of the lawful and organizational nature within the framework of social policy. The large potential of interaction of authority and NPO and the need for systems and integral approaches in its realization is asserted according to the results of a study.